Surgical training during the COVID-19 pandemic: preparing for future uncertainty. Issue 1 (January 2022) - Ellis, R.; Scrimgeour, D.S.G.; Brennan, P.A.
Abstract: The COVID-19 pandemic has brought unprecedented changes in healthcare and surgical training, with elective operating reduced or stopped, conferences rearranged and examinations cancelled. Trainees and trainers have adapted, creating innovative and resourceful ways to continue learning, enabling progression through surgical training. With rising COVID-19 cases across the world and further waves of infections likely, we reflect on recent changes to surgical training and discuss how best to support the next generation of surgeons during this period of uncertainty.